Patterns of body mass senescence and selective disappearance differ among three species of free-living ungulates. - Nussey, D; Coulson, T; Delorme, D; Clutton-Brock, T; Pemberton, J; Festa-Bianchet, M; Gaillard, J (2011)
Declines in survival and reproduction with age are prevalent in wild vertebrates, but we know little about longitudinal changes in behavioral, morphological, or physiological variables that may explain these demographic declines. We compared age-related variation in body mass of adult females in three free-living ungulate populations that have been the focus of long-term, individual-based research: bighorn sheep (Ovis canadensis) at Ram Mountain, Canada; roe deer (Capreolus capreolus) at Trois Fontaines, France; and Soay sheep (Ovis aries) on St. Kilda, Scotland. We use two recently proposed approaches to separate contributions to age-dependent variation at the population level from within-individual changes and between-individual selective disappearance. Selective disappearance of light individuals in all three populations was most evident at the youngest and oldest ages. In later adulthood, bighorn sheep and roe deer showed a continuous decline in body mass that accelerated with age while Soay sheep showed a precipitous decrease in mass in the two years preceding death. Our results highlight the importance of mass loss in explaining within-individual demographic declines in later adulthood in natural populations. They also reveal that the pattern of senescence, and potentially also the processes underlying demographic declines in late life, can differ markedly across related species with similar life histories.